MANAJEMEN TRANSFORMASI DIGITAL DALAM EFEKTIVITAS PELAYANAN AKADEMIK DI FAKULTAS TARBIYAH UNIVERSITAS ISLAM NEGERI SYEKH WASIL KEDIRI - Heru Kiswanto; Ismi Rohmattul Muslimah; Muhammad Fatichul Irsyad; Aulia Dini Afifatusholihah; Diki Darmawan (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the management of digital transformation in improving the effectiveness of academic services at the Faculty of Tarbiyah, UIN Syekh Wasil Kediri. The research was conducted using a qualitative case study method through interviews, observations, and document analysis, and the data were examined using Miles and Huberman’s interactive analysis model. The findings show that digital transformation was systematically planned through needs mapping, infrastructure strengthening, development of digital SOPs, human resource training, and the preparation of an information system roadmap. This planning stage aligns with the unfreezing phase in Kurt Lewin’s Change Management Theory, where old patterns are weakened and awareness of the need for change is built. In the implementation or changing phase, the adoption of integrated digital services led to real shifts in work culture, improved data processing speed, easier student access, and reduced administrative workload. The evaluation results indicate that the refreezing stage has been achieved, marked by faster service delivery, increased data accuracy, improved accessibility, fewer complaints, and the establishment of a more efficient and accountable digital work culture. Overall, digital transformation at the Faculty of Tarbiyah, UIN Syekh Wasil Kediri has reached a consolidation phase and has become an important foundation for modernizing academic governance.